Analisis Faktor - Faktor yang Berhubungan dengan Motivasi Kerja Perawat di Rumah Sakit Anna Bekasi - Aminah, Siti; Seltira, Seltira (Universitas Malahayati, 2025)
ABSTRACT Work motivation is a factor that really determines the level of employee performance and the quality of achieving goals, where nurses are the main resource and an important part in providing services in hospitals to achieve the desired targets. The aim of this research is to determine the factors that influence the work motivation of nurses at the Inpatient Anna Hospital Bekasi. The type of design that will be used in the research is quantitative with a correlational study research design. The approach that will be taken in the research uses a cross-sectional method. In the statistical test carried out by researchers, namely the Chi Square test. From the SPSS test results, it is known that nurses' work motivation between individuals has a POR value of 7.944 (95%CI= 2,013-31,347), between nurses' work motivation and rewards or fees with a POR value of 30,545 (95%CI= 3,556-262,389), and between nurses' work motivation and responsibility with a POR value of 8 (95%CI= 2062-31041). It can be concluded that there is a relationship between nurses' work motivation and relationships between individuals, rewards or rewards, and responsibility. Keywords: Nurse Work Motivation, Reward, Responsibility ABSTRAK Motivasi kerja merupakan faktor yang sangat menentukan tingkat kinerja karyawan dan kualitas pencapaian tujuan, dimana perawat sebagai sumber daya utama dan merupakan bagian penting dari pemberian layanan di rumah sakit untuk mencapai sebuah target yang diinginkan. Penelitian ini untuk mengetahui faktor- faktor yang mempengaruhi motivasi kerja perawat di Rawat Inap Rumah Sakit Anna Bekasi. Metode yang digunakan dalam penilitian yakni kuantitatif dengan rancangan penelitian correlation study. Pendekatan yang akan dilakukan dalam penelitian menggunakan cara cross-sectional.menggunakan kuesioner sebanyak 50 sempel. Dalam uji statistic yang dilakukan oleh peneliti yakni uji Chi Square. Uji SPSS didapatkan motivasi kerja perawat antar individual dengan nilai POR 7.944 (95%CI= 2,013-31,347), motivasi kerja perawat dengan reward atau fee dengan nilai POR 30,545 (95%CI= 3,556-262,389), dan antara motivasi kerja perawat dengan tanggung jawab dengan nilai POR 8 (95%CI= 2,062-31,041). Terdapat hubungan antara motivasi kerja perawat dengan kolerasi antar individua, reward atau fee, dan tanggung jawab. Kata Kunci: Motivasi Kerja Perawat, Reward, Tanggung Jawab